Festuca silana (Poaceae), a new species from the Sila plateau in Italy - Mattia Pallanza; Simone Orsenigo; Nicola Maria Giuseppe Ardenghi; Liliana Bernardo; Petr Šmarda; Petra Šarhanová; Graziano Rossi; Bruno Foggi (PhytoKeys)
A new hexaploid species of fine-leaved fescue from Festuca sect. Festuca (Festuca silana Ardenghi, Pallanza & Foggi, sp. nov.) endemic to the Sila plateau is described. The new taxon shows morphological affinities with species of the F. marginata group from which it can be distinguished by higher ploidy, ecology, and leaf cross section anatomy. ddRADseq data suggests F. silana could be a local hexaploid descendant/derivate of the widespread diploid F. marginata. Its distribution is restricted to several localities in the Sila highlands of the Southern Apennines, Italy.